The Impact of Social Media on Consumer Behavior Using Big Data Analytics - Saqiba Ehtesham (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Social media platforms like YouTube, Facebook, Instagram, and Twitter have revolutionized communication and information consumption. With billions of users, these platforms generate massive amounts of data for analysis. Big data analytics helps businesses predict consumer preferences, tailor marketing strategies, and improve experiences. However, the sheer volume of data presents challenges in analysis. Social media platforms facilitate information sharing for learning, innovation, branding, self-improvement, and customer involvement. This paper explores how social media posts influence decision-making using big data analytics